PROFESSIONAL PLAN AS A COMPONENT OF PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT FOR PROFESSIONAL SELF-DETERMINATION OF THE INDIVIDUAL (Psychology Travelogs, 2023)
The article is devoted to the topical issues of professional self-determination as a conscious choice of a life position by a subject and the person's awareness of himself/herself as a subject of a specific professional activity. The formation of professional plans is seen as a holistic and multidimensional process within the framework of professional self-determination, which is carried out in the context of vocational education and is aimed at designing stages and steps for self-realisation in social and chosen professional activities in accordance with the interests, aptitudes of the individual and the requirements of society and the labour market for a modern professional.A structural component of professional self-determination is the availability of a professional plan - a well-founded idea of the chosen field of work, ways to master the future profession and prospects for professional growth. A professional plan is an integral part of a life plan - a person's idea of the desired lifestyle, i.e. social, professional, family status, as well as the ways and means of achieving it.Studying the features of the plan makes it possible to consider the professional plan of an individual, firstly, as the result of a complex and synthetic process that includes the formation of a system of interrelated ideas about future professional activity; secondly, as a category that has a certain potential for dynamics, developing in stages; thirdly, as a set of well-founded ideas about the chosen field of work, ways of mastering the future profession, and prospects for professional growth.
Keywords: professional self-determination; psychological and pedagogical support; professional plan; subject; life position; professional activity